2020
DOI: 10.1111/evj.13208
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐user and intra‐user variation of two tonometers in horses

Abstract: Background It is currently unknown which of the two devices most commonly used in equine ophthalmology for intraocular pressure (IOP) estimation demonstrates the lowest inter‐user and intra‐user variation. Objectives To assess the inter‐user and intra‐user variation of two tonometers in sedated and unsedated horses. Study design Randomised masked cross‐over trial. Methods Four examiners used the rebound (ICare® TonoVet) and applanation (TonoPen®) tonometers to measure the intraocular pressure (IOP) in triplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…The mean readings of 21.0 ± 3.14 mmHg (CV ± 15.0%) obtained with Tonovet ® were only slightly lower than readings reported by Knollinger et al 6 of 22.1 ± 5.9 mmHg (CV ± 26.7%) in horses without sedation or auriculopalpebral (AP) block, and somewhat lower than readings reported by Holve et al 9 of 24.3 ± 3.09 mmHg (CV ± 12.7%) and Lewin et al 14 of 25.4 ± 7 mmHg (CV ± 27.6%) in horses without sedation but with AP block. The mean readings of 21.6 ± 2.45 mmHg (CV ± 11.3%) obtained with Tonovet Plus ® were very close to those reported by Knollinger et al 6 …”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The mean readings of 21.0 ± 3.14 mmHg (CV ± 15.0%) obtained with Tonovet ® were only slightly lower than readings reported by Knollinger et al 6 of 22.1 ± 5.9 mmHg (CV ± 26.7%) in horses without sedation or auriculopalpebral (AP) block, and somewhat lower than readings reported by Holve et al 9 of 24.3 ± 3.09 mmHg (CV ± 12.7%) and Lewin et al 14 of 25.4 ± 7 mmHg (CV ± 27.6%) in horses without sedation but with AP block. The mean readings of 21.6 ± 2.45 mmHg (CV ± 11.3%) obtained with Tonovet Plus ® were very close to those reported by Knollinger et al 6 …”
Section: Discussionmentioning
confidence: 48%
“…Tonovet ® rebound tonometer (Icare Finland) has been shown to provide accurate results with low interobserver variability in both human and animal patients, 11‐13 while Tono‐Pen ® applanation tonometer is more prone to inaccuracy due to incorrect technique 12 . A recent study showed significantly lower inter‐user and intra‐user variation in unsedated horses and lower intra‐user variation in sedated horses with Tonovet ® than with Tono‐Pen ® 14 . In dogs and cats, Tono‐Pen ® has been found to provide accurate readings in the physiological range of IOP, but has a tendency to underestimate IOP in the high range and to overestimate IOP in the low range 12,15 .…”
Section: Introductionmentioning
confidence: 99%
“…This study by Andrew Lewin and colleagues in the USA aimed to determine whether applanation or rebound tonometry has the lowest inter‐ and intra‐user variation when measuring intraocular pressure (IOP) in horses.…”
Section: Tonometrymentioning
confidence: 99%
“…In clinical practice, a more limited range from 15 to 30 mm Hg is generally accepted 6 . Estimation of IOP in horses is most commonly accomplished using handheld measurement devices that employ corneal applanation or rebound mechanisms 2,5,7 ; of these two modalities, rebound tonometry has demonstrated the least intra‐user variability in this species 8 …”
Section: Introductionmentioning
confidence: 99%